Early American literature : a comparatist approach - Aldridge, Alfred Owen, 1915-2005 (Princeton legacy library., 1982)
A. Owen Aldridge shows that early American literature is not an isolated phenomenon, but one affected by the same influences which operated upon other literatures of the period. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vas.